منهج تطويري مقترح في تعليم الإعراب للناطقين بغير العربية: الجملة في كتب النحو الحديثة نموذجا = Proposed developmental method in teaching I‘rab to non-speakers of Arabic: sentence in modern Arabic grammar books as case study = Cadangan metod berperingkat dalam pengajaran I‘rab kepada penutur bukan Arab: kajian kes ayat di dalam Buku nahu moden. - Sahrir, Muhammad Sabri; Mohamed Salem, Elsayed (Department of Arabic and Linguistic Studies, KIRKHS, International Islamic University Malaysia, 2018)
تعددت الشكاوى من صعوبة النحو قديماً وحديثاً؛ وبخاصة من متعلميه من الناطقين بغير العربية؛ إذ إن التيسير مطلب شرعي وأساسي تعليمياً، ولا يطلب إلا إذا استصعبت الأشياء، ومن هنا كان من الواجب اقتراح نموذج تطويري للإعراب الموروث ابتداء، وقابل للتطوير لاحقاً؛ ويمكن تطبيقه في قاعات الدرس، واتبعت الدراسة المنهج الوصفي التحليلي، وهدفت إلى تيسير النحو للناشئة الذي أصبح من الأمور الضرورية والحتمية التي لا مناص منها. توصلت الدراسة إلى ما يأتي: الأصل من تعليم النحو هو المحاكاة والتقليد، وليس الحفظ والترديد، وأن مهارة الإعراب تكتسب بالتدرب على العلاقة بين الكلمات، وليس على ترتيبها في الجملة، وصعوبة العربية تعود إلى طريقة عرض النحويين لقواعدها، وامتلاؤها بالجدل والخلافات العقيمة، وأن دراسة التراكيب في المراحل المبكرة لذو أثر كبير في نماء ذوق الطلبة وتنمية قدراتهم اللغوية، ويجب التفرقة بين النحو بمفهوم تقويم اللسان من اللحن، ومفهومه الذي يبحث عن العلل والأسباب والعوامل. ******************************************************** There were many complaints about the difficulty of grammar, in the past and present, especially among learners of non-Arabic native speakers. Thus, it should be facilitated as a important requirement and based on an educational basis, as it is required only if things are difficult. Hence, it was necessary to propose an enhanced model for the inherited declension, which is able to be expanded later for application in classrooms. There is no doubt that there is no magical way or secret idea for the students, which leads them directly to the desired goal, which is the composition ability of their sound pronunciation, and evaluate their tongues on the sound, but access to that valuable result is a combination of many factors enumerated research in this paper. The research presented descriptive analytical, ends with exercises on what was proposed. The goal is clear, and the way to it is in the content selection - arrangement - gradually, and then comes the good training based on the grounds of combining comprehensiveness and ease. If this achieved, research has become important in that it is a cycle of facilitation, and an idea of ​​the development ideas sought by the institutions concerned with educational curricula and development. ********************************************************** Terdapat banyak aduan mengenai kesukaran tatabahasa, baik yang lama atau baru, terutamanya di kalangan pelajar penutur asli bukan Arab. Oleh itu, isu ini merupakan satu keperluan yang penting berdasarkan kepada asas-asas pembelajaran di mana ianya hanya diperlukan dalam situasi sukar. Oleh itu, adalah perlu untuk mencadangkan model pembelajaran ‘irab’ yang dipertingkatkan untuk mengatasi masalah sedia ada, yang dapat diperluaskan kemudiannya untuk aplikasi dalam bilik-bilik darjah. Tidak menjadi keraguan bahawa tidak ada cara ajaib atau idea rahsia untuk pelajar, yang dapat membawa mereka mencapai matlamat yang diinginkan, yang merupakan keupayaan komposisi sebutan suara, menilai lidah mereka pada sebutan, tetapi hasil yang berjaya itu adalah gabungan banyak faktor yang dihuraikan dalam artikel ini. Kajian ini mengggunakan analisis deskriptif yang berakhir dengan metod latihan yang dicadangkan. Matlamatnya adalah jelas yang tertera dalam kandungan modul pemilihan - susunan - berperingkat, diikuti oleh latihan yang baik berdasarkan justifikasi gabungan secara menyeluruh dan mudah. Jika objektif modul ini dapat dicapai, kajian ini mempunyai manfaat bagi memudahkan dan mengembangkan kurikulum pengajaran yang dicari oleh institusi pendidikan.